Sodium electric single crystal layered positive electrode material precursor, preparation method thereof, positive electrode material and sodium ion battery

By controlling the ammonia concentration and pH value during co-precipitation, combined with the use of antioxidants, the particle agglomeration and segregation problems of sodium-electric precursors during co-precipitation are solved, and a single crystal positive electrode with uniform particle size and good spherical shape is prepared. Material precursor improves firing effect and circulation performance.

CN119240806APending Publication Date: 2025-01-03JINCHI ENERGY MATERIALS CO LTD +2

Patent Information

Application Number
CN202411454190.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

During the co-precipitation process, existing sodium-electric precursors have problems such as obvious particle agglomeration, thin primary particles and high difficulty in firing single crystals. In addition, zinc ions are prone to precipitation under the ammonia water system, resulting in uneven precipitation and segregation, affecting cycling performance.

Method used

By controlling the ammonia concentration and pH value during co-precipitation, the pH value of the reaction system is controlled in stages and the addition of antioxidants during the aging process, a thick-sized sheet-shaped primary particles with a particle size of 3.5~10.0μm are prepared. Secondary particle spheres or sphere-like precursors inhibit particle refinement and ion segregation, and improve the difficulty of firing of single-crystal positive electrode materials.

Benefits of technology

A single crystal positive electrode material precursor with uniform particle size and spherical shape is obtained, which reduces the difficulty of single crystal firing, improves the structure and performance of the positive electrode material, and improves the cyclic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240806A_ABST
    Figure CN119240806A_ABST
Patent Text Reader

Abstract

According to the sodium-electric single-crystal layered positive electrode material precursor and the preparation method thereof, the sodium-electric single-crystal layered positive electrode material and the sodium-ion battery, high alkalinity is controlled in the coprecipitation process, the pH value is controlled in stages, oxidation is strictly controlled in the reaction process and the aging process, and the sodium-ion battery performance is improved. The secondary particle sphere or sphere-like single crystal precursor with the particle size D50 of 3.5-10.0 mu m and uniformly distributed elements and composed of thick insertion sheet-shaped primary particles can be obtained, ion segregation and generation of fine particles can be well inhibited, subsequent firing of a single crystal positive electrode material is facilitated, the smoothness and roundness of single crystal particles are improved, and the preparation method is simple and convenient to operate. The sintering difficulty of the single-crystal positive electrode material is reduced, the structure and performance of the positive electrode material are improved, and the performance of the sodium ion battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery materials, and specifically relates to a sodium electric single crystal layered positive electrode material precursor and a preparation method thereof, a positive electrode material, and a sodium ion battery. Background Art

[0002] Over the past few decades, the industrialization of lithium-ion batteries has completely changed the world's energy landscape. However, the scarcity of raw materials required for lithium-ion batteries, coupled with the current surge in demand for lithium-ion batteries in electric vehicles, has limited the application of lithium-ion batteries in large-scale energy storage. Therefore, sodium-ion batteries with similar electrochemical properties to lithium-ion batteries have been proposed, and sodium resources are widely distributed around the world, which can greatly reduce the cost of materials. Among the positive electrode materials of sodium-ion batteries, layered transition metal oxide materials Na x TMO2 (TM usually represents one or more elements such as Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Li, etc.) has great application prospects due to its excellent electrochemical properties.

[0003] Cathode materials play a crucial role in sodium-ion batteries, determining their cost. Currently, layered oxide cathode materials are the mainstream cathode materials for sodium-ion batteries, offering advantages such as low cost, moderate specific capacity, and excellent cycle performance. These excellent overall properties make layered sodium-ion cathode materials promising for development and application. Sodium-ion batteries based on these cathode materials have the potential to be used in low-end electric vehicles and large-scale energy storage applications.

[0004] Co-precipitation is a commonly used method for preparing layered oxide precursors. This method offers advantages such as low cost, easy morphology control, and low energy consumption. For example, the nickel-cobalt-manganese precursor for lithium-ion batteries, a ternary material, is primarily prepared by using atmosphere protection, ammonia complexation, and controlled crystallization to ultimately produce a nickel-cobalt-manganese hydroxide precursor.

[0005] However, the current doped sodium battery precursors have defects in morphology and physical properties, mainly including: ① obvious particle agglomeration; ② the primary particles are thin and single crystal firing is difficult. Summary of the Invention

[0006] In response to the above technical problems, the present application provides a sodium electric single crystal layered cathode material precursor and a preparation method thereof, a sodium electric single crystal layered cathode material, and a sodium ion battery. To achieve the above objectives, this application proposes the following solutions: In the first aspect, a sodium electric single crystal layered cathode material precursor is provided, wherein the chemical formula of the precursor is Ni x Fe y M (1-x-y-z) Mn z(OH)2, wherein 0.2≤x≤0.4, 0.2≤y≤0.5, 0.2≤z≤0.5, 0≤1-xyz≤0.1, and M is one or more of Cu, Zn, Ca, Mg, Al, Cr, and Cd; the precursor is a secondary particle sphere or spheroid composed of flake-shaped primary particles; and the particle size D50 of the precursor is 3.5~10.0 μm.

[0007] Preferably, 0.03≤1-xyz≤0.08.

[0008] Preferably, M is one or more of Cu and Zn.

[0009] Preferably, the particle size D50 of the precursor is 3.5-7.0 μm.

[0010] In a second aspect, a method for preparing a sodium electric single crystal layered cathode material precursor is provided, comprising: (1) A mixed metal salt solution, an alkali solution and a complexing agent solution are simultaneously introduced into the bottom liquid of a reactor to carry out a coprecipitation reaction; in the mixed metal salt solution, the metal elements are arranged according to Ni x Fe y M (1-x-y-z) Mn z Ratio, wherein 0.2≤x≤0.4, 0.2≤y≤0.5, 0.2≤z≤0.5, 0≤1-xyz≤0.1, M is one or more of Cu, Zn, Ca, Mg, Al, Cr, Cd; wherein an antioxidant is added to the mixed metal sulfate solution; The coprecipitation reaction includes a nucleation stage and a particle growth stage. During the coprecipitation reaction, the ammonia concentration of the reaction system is controlled to be 7-15 g / L; the pH value of the reaction system is controlled to be 11.00-11.40 during the nucleation stage; and the pH value of the reaction system is controlled to be 10.30-11.20 during the particle growth stage until the precursor seed material grows to a target particle size D50 to obtain a sodium electrode precursor slurry; the pH value of the reaction system in the nucleation stage is higher than the pH value of the reaction system in the particle growth stage; (2) aging the precursor slurry, adding an antioxidant during the aging process, and continuously stirring. After the aging is completed, solid-liquid separation, washing and drying are performed to obtain the product. Preferably, in step (1), the antioxidant in the mixed metal salt solution is one or more of ascorbic acid, sodium citrate, isoascorbic acid and sodium isoascorbate; 0.15-0.3 g of antioxidant is added per 1 L of the mixed metal salt solution, and more preferably, 0.20-0.30 g of antioxidant is added per 1 L of the mixed metal salt solution.

[0011] Preferably, in step (2), the antioxidant is ascorbic acid; and during the aging process, 0.30-0.75 g of antioxidant is added per 1 L of the aged slurry, and more preferably, 0.35-0.50 g of antioxidant is added per 1 L of the aged slurry.

[0012] Preferably, in step (1), an antioxidant is added to the bottom liquid of the reactor; the antioxidant is ascorbic acid; 0.15-0.5 g of antioxidant is added to every 1 L of the bottom liquid of the reactor, and more preferably, 0.2-0.35 g of antioxidant is added to every 1 L of the bottom liquid of the reactor.

[0013] Preferably, in step (1), the alkalinity of the reactor bottom liquid is 7-15.0 g / L, the pH value is 11.00-11.40, and the temperature is 50±5°C.

[0014] Preferably, in step (1), the pH of the reaction system in the nucleation stage is 0.2-0.6 higher than the pH of the reaction system in the particle growth stage.

[0015] Preferably, in step (1), the flow rate of the mixed metal salt solution in the nucleation stage is 60-100 ml / min.

[0016] Preferably, in step (1), the flow rate of the mixed metal salt solution in the particle growth stage is 120~240 ml / min.

[0017] Preferably, nitrogen is introduced in both step (1) and step (2) for protection.

[0018] Preferably, in step (1) and step (2), the temperature of the reaction system is controlled to be 50-55° C., and the stirring speed is controlled to be 200-500 r / min. Preferably, in step (1), the target particle size D50 of the precursor seed material in the nucleation stage is 0.5-1.8 μm; and the reaction time of the nucleation reaction is 0.5-3.5 h.

[0019] In a third aspect, a sodium electric single crystal layered positive electrode material is provided, which is obtained by sintering the aforementioned precursor or the precursor prepared by the aforementioned preparation method with mixed sodium.

[0020] In a fourth aspect, a sodium-ion battery is provided, comprising the aforementioned sodium-ion single crystal layered positive electrode material.

[0021] Compared with the prior art, this application has the following beneficial effects: The present application controls high alkalinity and pH value in stages during the co-precipitation process, and strictly controls oxidation during the reaction process and aging, thereby obtaining secondary particle spheres or spherical single crystal precursors with a particle size D50 of 3.5~10.0μm, uniform element distribution, and composed of thick flaky primary particles. The sphericity is good, which can effectively inhibit particle refinement, ion segregation and the generation of fine particles, is beneficial to the subsequent firing of single crystal positive electrode materials, and is beneficial to improving the smoothness and roundness of single crystal particles, reducing the difficulty of firing single crystal positive electrode materials, and improving the structure and performance of positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0023] Figure 1 This is the SEM image of the sodium electrode precursor obtained in Comparative Example 1. Figure 2 This is the SEM image of the sodium electrode precursor obtained in Comparative Example 2.

[0024] Figure 3 This is the SEM image of the sodium electrode precursor obtained in Example 1.

[0025] Figure 4 This is the SEM image of the sodium electrode precursor obtained in Example 2.

[0026] Figure 5 This is the SEM image of the sodium electrode precursor obtained in Example 3.

[0027] Figure 6 This is the SEM image of the sodium electrode precursor obtained in Example 4.

[0028] Figure 7 This is the SEM image of the sodium electrode precursor obtained in Comparative Example 3.

[0029] Figure 8 This is the SEM image of the sodium electrode precursor obtained in Comparative Example 4.

[0030] Figure 9 This is the SEM image of the sodium electrode precursor obtained in Comparative Example 5.

[0031] Figure 10 This is the SEM image of the sodium electrode precursor obtained in Comparative Example 6.

[0032] Figure 11 This is the SEM image of the sodium electrode precursor obtained in Comparative Example 7.

[0033] Figure 12 This is the SEM image of the sodium electrode precursor obtained in Comparative Example 8. DETAILED DESCRIPTION

[0034] Some embodiments of the present invention provide a sodium electric single crystal layered cathode material precursor, the chemical formula of which is Ni x Fe y M (1-x-y-z) Mn z (OH)2, wherein 0.2≤x≤0.4, 0.2≤y≤0.5, 0.2≤z≤0.5, 0≤1-xyz≤0.1, and M is one or more of Cu, Zn, Ca, Mg, Al, Cr, and Cd; the precursor is a secondary particle sphere or spheroid composed of thick flaky primary particles; and the particle size D50 of the precursor is 3.5~10.0 μm.

[0035] Precursors with good sphericity and thick, flake-like primary particles are beneficial for sintering single-crystal cathode particles with uniform morphology and size. Larger particles make them less likely to break during single crystal sintering, resulting in poor single-crystal formation. However, smaller particles result in a low tap density, hollow secondary particles, and thin primary particles, making it difficult to form single crystals during sintering of the cathode material.

[0036] In some preferred embodiments, 0.03≤1-xyz≤0.08, and more preferably 0.03≤1-xyz≤0.06.

[0037] In some preferred embodiments, M is one or more of Cu and Zn; zinc is doped mainly to improve the structural stability and capacity of the material.

[0038] In some preferred embodiments, the particle size D50 of the precursor is 3.5-7.0 μm, more preferably 5.0-7.0 μm.

[0039] Some embodiments of the present invention provide a method for preparing a sodium-ion battery single crystal layered cathode material precursor, comprising: (1) A mixed metal salt solution, an alkali solution and a complexing agent solution are simultaneously introduced into the bottom liquid of a reactor to carry out a coprecipitation reaction; in the mixed metal salt solution, the metal elements are arranged according to Ni x Fe y M (1-x-y-z) Mn z Ratio, wherein 0.2≤x≤0.4, 0.2≤y≤0.5, 0.2≤z≤0.5, 0≤1-xyz≤0.1, M is one or more of Cu, Zn, Ca, Mg, Al, Cr, Cd; wherein an antioxidant is added to the mixed metal salt solution; The coprecipitation reaction includes a nucleation stage and a particle growth stage. During the coprecipitation reaction, the ammonia concentration of the reaction system is controlled to be 7-15 g / L. The pH of the reaction system is controlled to be 11.00-11.40 in the nucleation stage to obtain a precursor seed material. The pH of the reaction system is controlled to be 10.30-11.20 in the particle growth stage until the precursor seed material grows to a target particle size D50 to obtain a sodium electrode precursor slurry. The pH of the reaction system in the nucleation stage is higher than the pH of the reaction system in the particle growth stage. (2) aging the precursor slurry, adding an antioxidant during the aging process, and continuously stirring. After the aging is completed, solid-liquid separation, washing and drying are performed to obtain the product. The current sodium electric single crystal precursor is prone to obvious particle agglomeration and thin primary particles, which makes single crystal firing difficult. In the research process, the applicant found that in the preparation of nickel iron zinc manganese precursors, zinc ions are very easy to precipitate in the ammonia system and become crystal nuclei alone. Zinc hydroxide is amphoteric and will dissolve at a high pH value, while iron ions are easily oxidized. Therefore, during the co-precipitation process, there are problems such as uneven precipitation and serious segregation of iron and zinc (when zinc and iron are unevenly precipitated, there will be enrichment, and then enriched segregation will occur, resulting in deviations in the particle growth trend and changes in the sample morphology). The circulation process is prone to separate precipitation, affecting the circulation. In response to these technical problems, the applicant has conducted research and achieved good co-precipitation of metal ions in the metal mixed salt solution by regulating the ammonia concentration and pH of the co-precipitation process. After co-precipitation, the solution is aged and certain antioxidant measures are adopted during the reaction process to prepare secondary particle spheres or spherical-like precursors with a particle size D50 of 3.5~10.0μm, uniform element distribution, and composed of thick flaky primary particles.

[0040] During the research process, the applicant also found that during the aging process, there is a problem that fine particles are easily formed on the sample surface, which is not conducive to the firing of single crystal positive electrode materials. To address this technical problem, the applicant conducted research and effectively eliminated these fine particles by adding a certain amount of antioxidants during the aging process, thereby further improving the sample morphology.

[0041] During the coprecipitation reaction, the ammonia concentration of the reaction system is controlled to be 7-15 g / L, for example, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, etc.

[0042] During the nucleation stage, the pH of the reaction system is controlled to be 11.00-11.40, for example, 11.10, 11.20, 11.30, 11.40, etc.

[0043] During the particle growth stage, the pH value of the reaction system is controlled to be 10.30-11.20, for example, 10.30, 10.40, 10.50, 10.60, 10.70, 10.80, 10.90, 11.00, 11.10, 11.20, 11.30, 11.40, etc.

[0044] In some preferred embodiments, 0.03≤1-xyz≤0.08, and more preferably 0.03≤1-xyz≤0.06.

[0045] In some preferred embodiments, M is preferably one or more of Cu and Zn.

[0046] In some preferred embodiments, in step (1), the antioxidant in the mixed metal salt solution is one or more of ascorbic acid, sodium citrate, isoascorbic acid and sodium isoascorbate; 0.15-0.3 g of antioxidant is added to each 1 L of the mixed metal salt solution, and more preferably, 0.20-0.30 g of antioxidant is added to each 1 L of the mixed metal salt solution, for example, 0.20 g, 0.22 g, 0.24 g, 0.26 g, 0.28 g, 0.30 g, etc.

[0047] In some preferred embodiments, in step (2), the antioxidant is ascorbic acid; during the aging process, 0.30-0.75 g of antioxidant is added per 1 L of the aged slurry, and more preferably, 0.35-0.5 g of antioxidant is added per 1 L of the aged slurry, for example, 0.35 g, 0.38 g, 0.40 g, 0.42 g, 0.45 g, 0.47 g, 0.50 g, etc.

[0048] In some preferred embodiments, in step (1), an antioxidant is added to the bottom liquid of the reactor; the antioxidant is ascorbic acid; 0.15-0.5 g of antioxidant is added per 1 L of the bottom liquid of the reactor, and more preferably, 0.2-0.35 g of antioxidant is added per 1 L of the bottom liquid of the reactor, for example, 0.20 g, 0.22 g, 0.24 g, 0.26 g, 0.28 g, 0.30 g, 0.32 g, 0.35 g, etc.

[0049] In some preferred embodiments, in step (1), the alkalinity of the reactor bottom liquid is 7-15.0 g / L, the pH value is 10.30-11.40, and the temperature is 50±5° C. The reactor bottom liquid is prepared using water, ammonia water, sodium hydroxide, and an antioxidant.

[0050] In some preferred embodiments, in step (1), the pH of the reaction system in the nucleation stage is 0.2 to 0.6 higher than the pH of the reaction system in the particle growth stage, for example, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, etc.

[0051] In some preferred embodiments, nitrogen protection is introduced in both step (1) and step (2).

[0052] In some preferred embodiments, in step (1) and step (2), the temperature of the reaction system is controlled to be 50-55°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, etc.; if the reaction temperature is too high, the reaction activity will be increased, resulting in an increase in seed material; if the reaction temperature is too low, the reaction activity will be insufficient.

[0053] In some preferred embodiments, in step (1) and step (2), the stirring speed of the reaction system is controlled to be 200-500 rpm, for example, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, etc.

[0054] In some preferred embodiments, in step (1), the flow rate of the mixed metal salt solution in the nucleation stage is 60-100 ml / min, for example, 60 ml / min, 80 ml / min, 100 ml / min, etc.

[0055] In some preferred embodiments, in step (1), the flow rate of the mixed metal salt solution during the particle growth stage is 120-240 ml / min.

[0056] In some preferred embodiments, in step (1), the stirring speed in the nucleation stage is 400-500 rpm, for example, 400 rpm, 420 rpm, 450 rpm, 480 rpm, 500 rpm, etc.

[0057] In some embodiments, in step (1), in the particle growth stage, the flow rate of the metal salt in the first stage is 120~160ml / min, the stirring speed is 400~450rpm, and the reaction time of the first stage is 3~6h; the flow rate of the metal salt in the second stage is 160~240ml / min, the stirring speed is 350~400rpm, and the reaction time of the second stage is 20~40h; and the flow rate in the first stage is lower than that in the second stage, and the speed in the first stage is higher than that in the second stage; the ratio of the flow rate increase is 40~60%; and the ratio of the speed decrease is 10~20%.

[0058] In some preferred embodiments, in step (1), the target particle size D50 of the precursor seed material in the nucleation stage is 0.5-1.8 μm, more preferably 0.7-1.5 μm, and even more preferably 0.8-1.2 μm.

[0059] In some preferred embodiments, in step (2), the reaction time of the nucleation reaction is 0.5 to 3.5 hours, more preferably 2 to 3.5 hours.

[0060] The aging agent is sodium hydroxide solution, and the concentration can be a conventional concentration, for example, a concentration of 10wt%, and the addition ratio is related to the volume of the slurry tank.

[0061] In the above preparation method, the concentration of the mixed metal salt solution, the complexing agent concentration, and the alkali solution concentration can all be the same as those used in conventional coprecipitation preparation processes in the art. In some embodiments, the total metal molar concentration in the mixed metal salt solution is 0.5 to 4.0 mol / L, more preferably 1.0 to 4.0 mol / L. The mixed metal salt is any one or more of sulfate, nitrate, and acetate. In some embodiments, the complexing agent solution is an ammonia complexing agent solution with a concentration of 6 to 12 mol / L. In some embodiments, the alkali solution is a sodium hydroxide solution with a concentration of 6 to 12 mol / L.

[0062] In some preferred embodiments, during the reaction of step (2), the rate of concentrated supernatant liquid is consistent with the total feed flow rate to ensure stable clearing without overflowing the tank. In some embodiments, during the aging process, the stirring time is continuous for 30 to 60 minutes.

[0063] In some preferred embodiments, in step (4), the solid-liquid separation method is filter pressing; the acceptance criterion for the filter pressing is that the water content of the filter cake is less than 15%.

[0064] In some preferred embodiments, in step (4), the qualified criterion for washing is that the sulfate content is less than 0.4%.

[0065] In some preferred embodiments, in step (4), the acceptance criterion for drying is that the moisture content is less than 0.5%.

[0066] Some embodiments of the present invention provide a sodium electric single crystal layered cathode material, which is obtained by sintering the aforementioned precursor or the precursor prepared by the aforementioned preparation method with sodium.

[0067] Some embodiments of the present invention provide sodium-ion batteries, comprising the aforementioned sodium-ion single crystal layered cathode material.

[0068] To facilitate understanding of the present invention, the present invention will be described in more comprehensive and detailed form below in conjunction with the accompanying drawings and preferred embodiments. However, the scope of protection of the present invention is not limited to the following specific embodiments.

[0069] Comparative Example 1 A method for preparing a sodium-ion layered cathode material precursor comprises the following steps: (1) Solution preparation stage: According to the molar ratio of Ni:Zn:Fe:Mn of 23:8:33:36, a mixed metal sulfate solution of nickel, zinc, iron and manganese was prepared, and the total metal molar concentration in the solution was 2.0 mol / L; an ammonia solution was prepared as a complexing agent solution, and the concentration of the ammonia solution was 8.0 mol / L; a sodium hydroxide solution was prepared as a precipitant solution, and the concentration of the sodium hydroxide solution was 10.5 mol / L.

[0070] (2) Synthesis preparation stage: Add pure water to the synthesis reactor to the set liquid level, start stirring, and add sodium hydroxide solution and ammonia solution at the same time. Finally, adjust the bottom liquid conditions of the reactor to alkalinity 15.0 g / L, pH 11.40, temperature 50 °C, rotation speed 500 rpm and introduce nitrogen protection.

[0071] (3) Co-precipitation reaction stage: nickel, zinc, iron and manganese mixed metal salt solution, precipitant solution and complexing agent solution are added into the reactor in parallel to carry out co-precipitation reaction. Nitrogen protection is introduced during the co-precipitation reaction. The temperature of the reaction system is maintained at 50±0.5℃ during the co-precipitation process. The coprecipitation was divided into a nucleation stage and a particle growth stage. During the nucleation stage, the flow rate of the nickel-zinc-iron-manganese solution was 80 mL / min, the nucleation pH was maintained at 11.20±0.2, the alkalinity was 15 g / L, the rotation speed was 500 rpm, and the nucleation reaction time was 2.5 h, resulting in precursor particles with a particle size D50 of 1.5-1.7 μm. The pH value in the crystal nucleus growth stage was maintained at 10.80±0.1, and the alkalinity was 15.0 g / L. The flow rate in the particle growth stage was divided into two sections. The metal salt flow rate in the first section was 140 ml / min, the rotation speed was 450 rpm, and the growth time was 6 h. The metal salt flow rate in the second section was 200 ml / min, the rotation speed was 400 rpm, and the growth time was 40 h.

[0072] (4) Post-processing: After the particle size D50 of the reaction slurry reaches 6.0 μm, the reaction slurry is aged. During the aging process, 100 L of 10 wt% sodium hydroxide solution is added and stirred continuously for 20 min. After filtration, the solid phase is dried to obtain a precursor for the sodium ion layered cathode material. The acceptance criteria for filter pressing are that the filter cake has a water content of less than 15%, and the acceptance criteria for drying are that the water content is less than 0.5%.

[0073] The SEM image of the obtained precursor is shown in Figure 1 As shown, from Figure 1 It can be seen that the sphericity of the sample is poor, and there are obvious flaky primary particles, and a large number of fragmented particles produced by oxidation are attached to the surface of the primary particles.

[0074] Comparative Example 2 A method for preparing a sodium-ion layered cathode material precursor comprises the following steps: (1) Solution preparation stage: According to the molar ratio of Ni:Zn:Fe:Mn of 23:8:33:36, a mixed metal sulfate solution of nickel, zinc, iron and manganese was prepared, and ascorbic acid was added to the solution at a concentration of 0.277 g / L. The total metal molar concentration in the solution was 2.0 mol / L. Ammonia solution was prepared as a complexing agent solution at a concentration of 8.0 mol / L. Sodium hydroxide solution was prepared as a precipitant solution at a concentration of 10.5 mol / L.

[0075] (2) Synthesis preparation stage: The synthesis reactor was started with stirring, and pure water was added to the set liquid level. At the same time, sodium hydroxide solution and ammonia solution were added. Finally, the bottom liquid conditions of the reactor were adjusted to alkalinity 15.0 g / L, pH 11.40, and temperature 50 °C. Nitrogen was introduced for protection. Ascorbic acid was added to the bottom liquid of the reactor at a concentration of 0.3 g / L.

[0076] (3) Co-precipitation reaction stage: nickel, zinc, iron and manganese mixed metal salt solution, precipitant solution and complexing agent solution are added into the reactor in parallel to carry out co-precipitation reaction. Nitrogen protection is introduced during the co-precipitation reaction. The temperature of the reaction system is maintained at 50±0.5℃ during the co-precipitation process. The co-precipitation is divided into a nucleation stage and a particle growth stage; in the nucleation stage, the flow rate of the nickel-zinc-iron-manganese solution is 80 ml / min, the nucleation pH is maintained at 11.20±0.2, the alkalinity is 15 g / L, the rotation speed is 500 rpm, the nucleation stage time is 2.5 h, and precursor particles with a particle size D50 of 1.5~1.7 μm are obtained.

[0077] During the crystal nucleus growth stage, the pH was maintained at 10.80±0.1 and the alkalinity was 15.0 g / L. The flow rate during the particle growth stage was divided into two sections. The metal salt flow rate in the first section was 140 ml / min, the stirring speed was 450 rpm, and the reaction time was 6 h. The metal salt flow rate in the second section was 200 ml / min, the speed was 400 rpm, and the reaction time was 40 h.

[0078] (4) Post-processing: After the particle size D50 of the reaction slurry reaches 6.0 μm, the reaction slurry is aged. During the aging process, 100 L of 10 wt% sodium hydroxide solution is added and stirred continuously for 20 min. After filtration, the solid phase is dried to obtain a precursor for the sodium ion layered cathode material. The acceptance criteria for filter pressing are that the filter cake has a water content of less than 15%, and the acceptance criteria for drying are that the water content is less than 0.5%.

[0079] The SEM image of the obtained precursor is shown in Figure 2 As shown, from Figure 2 It can be seen that the addition of antioxidants at the initial stage of feeding is beneficial to alleviating the oxidation of iron ions during nucleation. The inhibition of oxidation is beneficial to the growth of thick flakes of primary particles during the co-precipitation process, while reducing the individual precipitation of iron ions, which is more conducive to co-precipitation nucleation and zinc-iron co-precipitation during crystal nucleus growth. However, there are still many fine particles attached to the surface of the sample, and these fine particles may affect the sintering effect of the positive electrode.

[0080] Example 1 A method for preparing a sodium-ion layered cathode material precursor comprises the following steps: (1) Solution preparation stage: According to the molar ratio of Ni:Zn:Fe:Mn of 23:8:33:36, a mixed metal sulfate solution of nickel, zinc, iron and manganese was prepared, and ascorbic acid was added at a concentration of 0.277 g / L (i.e., 0.277 g ascorbic acid was added to every 1 L of mixed metal sulfate solution). The total metal molar concentration in the solution was 2.0 mol / L; an ammonia solution was prepared as a complexing agent solution with a concentration of 8.0 mol / L; a sodium hydroxide solution was prepared as a precipitant solution with a concentration of 10.5 mol / L.

[0081] (2) Synthesis preparation stage: Pure water was added to the synthesis reactor to the set liquid level, stirring was started, and sodium hydroxide solution and ammonia solution were added at the same time. Finally, the bottom liquid conditions of the reactor were adjusted to alkalinity of 15.0 g / L, pH value of 11.40, temperature of 50 °C, and nitrogen protection was introduced. Ascorbic acid was added to the bottom liquid of the reactor at a concentration of 0.3 g / L (i.e., 0.3 g ascorbic acid was added to every 1 L of bottom liquid of the reactor). (3) Co-precipitation reaction stage: nickel, zinc, iron and manganese mixed metal salt solution, precipitant solution and complexing agent solution are added into the reactor in parallel to carry out co-precipitation reaction. Nitrogen protection is introduced during the co-precipitation reaction. The temperature of the reaction system is maintained at 50±0.5℃ and the alkalinity is 15g / L during the co-precipitation process.

[0082] The co-precipitation is divided into a nucleation stage and a particle growth stage; in the nucleation stage, the flow rate of the nickel-zinc-iron-manganese solution is 80 ml / min, the nucleation pH is maintained at 11.00±0.2, the rotation speed is 500 rpm, the reaction time is 2.5 h, and precursor particles with a particle size D50 of 1.5~1.7 μm are obtained.

[0083] During the crystal nucleus growth stage, the pH was maintained at 10.80±0.1 and the alkalinity was 15.0 g / L. The flow rate during the particle growth stage was divided into two sections. The metal salt flow rate in the first section was 140 ml / min, the stirring speed was 450 rpm, and the reaction time was 6 h. The metal salt flow rate in the second section was 200 ml / min, the speed was 400 rpm, and the reaction time was 40 h.

[0084] (4) Post-treatment stage: After the particle size D50 of the reaction slurry reaches 6.0 μm, the reaction slurry is aged. During the aging process, 100 L of 5 wt% sodium hydroxide solution is added, and the aging stirring time is increased to 30 min. Ascorbic acid is added to the reaction slurry according to the initial concentration of ascorbic acid in the slurry of 0.5 g / L (i.e., 0.5 g of ascorbic acid is added to every 1 L of reaction slurry). The addition of antioxidants is mainly to inhibit the irreversible oxidation of undissociated metal ions under the binding of ammonium ions during the aging process at room temperature. After filtration, the solid phase is dried to obtain a precursor for sodium ion layered positive electrode materials. Among them, the qualified standard for filter pressing is that the water content of the filter cake is less than 15%, and the qualified standard for drying is that the water content is less than 0.5%.

[0085] The SEM image of the obtained precursor is shown in Figure 3 As shown, from Figure 3 It can be seen that with the decrease of pH point during nucleation, the dissolution of zinc ions after precipitation is inhibited to a certain extent, the sphericity of the particles is better, and the thick flake shape of the primary particles is more obvious. In addition, when the alkali concentration is reduced and the aging time is prolonged during aging, and a certain amount of antioxidant is added, the effect of removing fine particles attached to the surface of the particles is more obvious, and the particle morphology is a spherical body with thick flakes and inserts.

[0086] Example 2 A method for preparing a sodium-ion layered cathode material precursor comprises the following steps: (1) Solution preparation stage: According to the molar ratio of Ni:Zn:Fe:Mn of 23:8:33:36, a mixed metal sulfate solution of nickel, zinc, iron and manganese was prepared, and ascorbic acid was added. 0.277g of ascorbic acid was added to each 1L of mixed metal sulfate solution, and the total metal molar concentration in the solution was 2.0mol / L; an ammonia solution was prepared as a complexing agent solution, and the concentration of the ammonia solution was 8.0mol / L; a sodium hydroxide solution was prepared as a precipitant solution, and the concentration of the sodium hydroxide solution was 10.5mol / L.

[0087] (2) Synthesis preparation stage: Pure water was added to the synthesis reactor to the set liquid level, stirring was started, and sodium hydroxide solution and ammonia solution were added at the same time. Finally, the bottom liquid conditions of the reactor were adjusted to alkalinity of 13.0 g / L, pH value of 11.20, and temperature of 50 °C. Nitrogen was introduced for protection, and ascorbic acid was added to the bottom liquid of the reactor at a concentration of 0.3 g / L (i.e., 0.3 g ascorbic acid was added to every 1 L of bottom liquid of the reactor). (3) Co-precipitation reaction stage: nickel, zinc, iron and manganese mixed metal salt solution, precipitant solution and complexing agent solution are added into the reactor in parallel to carry out co-precipitation reaction. Nitrogen protection is introduced during the co-precipitation reaction. The temperature of the reaction system is maintained at 50±0.5℃ and the alkalinity is 13g / L during the co-precipitation process.

[0088] The co-precipitation is divided into a nucleation stage and a particle growth stage; in the nucleation stage, the flow rate of the nickel-zinc-iron-manganese solution is 80 ml / min, the nucleation pH is maintained at 11.10-11.20, the rotation speed is 500 rpm, the reaction time is 2.5 h, and precursor particles with a particle size D50 of 1.5~1.7 μm are obtained.

[0089] During the crystal nucleus growth stage, the pH was maintained at 10.70-10.90, and the alkalinity was 13.0 g / L. The flow rate during the particle growth stage was divided into two sections. The metal salt flow rate in the first section was 140 ml / min, the stirring speed was 450 rpm, and the reaction time was 6 h. The metal salt flow rate in the second section was 200 ml / min, the speed was 400 rpm, and the reaction time was 40 h.

[0090] (4) Post-treatment stage: After the particle size D50 of the reaction slurry reaches 6.0 μm, the reaction slurry is aged. During the aging process, 100 L of 5 wt% sodium hydroxide solution is added, and the aging stirring time is increased to 30 min. Ascorbic acid is added to the reaction slurry according to the initial concentration of ascorbic acid in the slurry of 0.5 g / L (i.e., 0.5 g of ascorbic acid is added to every 1 L of reaction slurry). The addition of antioxidants is mainly to inhibit the irreversible oxidation of undissociated metal ions under the binding of ammonium ions during the aging process at room temperature. After filtration, the solid phase is dried to obtain a precursor for sodium ion layered positive electrode materials. Among them, the qualified standard for filter pressing is that the water content of the filter cake is less than 15%, and the qualified standard for drying is that the water content is less than 0.5%.

[0091] The SEM image of the obtained precursor is shown in Figure 4 As shown, from Figure 4 It can be seen that the sample is in the form of thick flakes and inserts in the primary particles, and spherical in the secondary particles.

[0092] Example 3 A method for preparing a sodium-ion layered cathode material precursor comprises the following steps: (1) Solution preparation stage: According to the molar ratio of Ni:Zn:Fe:Mn of 23:8:33:36, a mixed metal sulfate solution of nickel, zinc, iron and manganese was prepared, and ascorbic acid was added. 0.2g of ascorbic acid was added to each 1L of mixed metal sulfate solution, and the total metal molar concentration in the solution was 2.0mol / L; an ammonia solution was prepared as a complexing agent solution, and the concentration of the ammonia solution was 8.0mol / L; a sodium hydroxide solution was prepared as a precipitant solution, and the concentration of the sodium hydroxide solution was 10.5mol / L.

[0093] (2) Synthesis preparation stage: Pure water was added to the synthesis reactor to the set liquid level, stirring was started, and sodium hydroxide solution and ammonia solution were added at the same time. Finally, the bottom liquid conditions of the reactor were adjusted to alkalinity 15.0 g / L, pH 11.40, and temperature 50 °C. Nitrogen was introduced for protection, and ascorbic acid was added to the bottom liquid of the reactor at a concentration of 0.2 g / L. (3) Co-precipitation reaction stage: nickel, zinc, iron and manganese mixed metal salt solution, precipitant solution and complexing agent solution are added into the reactor in parallel to carry out co-precipitation reaction. Nitrogen protection is introduced during the co-precipitation reaction. The temperature of the reaction system is maintained at 50±0.5℃ and the alkalinity is 15g / L during the co-precipitation process.

[0094] The co-precipitation is divided into a nucleation stage and a particle growth stage; in the nucleation stage, the flow rate of the nickel-zinc-iron-manganese solution is 80 ml / min, the nucleation pH is maintained at 11.30-11.40, the rotation speed is 500 rpm, the reaction time is 2.5 h, and precursor particles with a particle size D50 of 1.5~1.7 μm are obtained.

[0095] During the crystal nucleus growth stage, the pH was maintained at 10.90-11.10, and the alkalinity was 15.0 g / L. The flow rate during the particle growth stage was divided into two sections. The metal salt flow rate in the first section was 140 ml / min, the stirring speed was 450 rpm, and the reaction time was 6 h. The metal salt flow rate in the second section was 200 ml / min, the speed was 400 rpm, and the reaction time was 40 h.

[0096] (4) Post-treatment stage: After the particle size D50 of the reaction slurry reaches 6.0 μm, the reaction slurry is aged. During the aging process, 100 L of 5 wt% sodium hydroxide solution is added, and the aging stirring time is increased to 30 min. Ascorbic acid is added to the reaction slurry according to the initial concentration of ascorbic acid in the slurry of 0.35 g / L (i.e., 0.35 g of ascorbic acid is added to every 1 L of reaction slurry). The addition of antioxidants is mainly to inhibit the irreversible oxidation of undissociated metal ions under the binding of ammonium ions during the aging process at room temperature. After filtration, the solid phase is dried to obtain a precursor for sodium ion layered positive electrode materials. Among them, the qualified standard for filter pressing is that the water content of the filter cake is less than 15%, and the qualified standard for drying is that the water content is less than 0.5%.

[0097] The SEM image of the obtained precursor is shown in Figure 5 As shown, from Figure 5 It can be seen that the prepared samples have good sphericity, with primary particles in the shape of thick flakes and inserts, and secondary particles in the shape of spheres.

[0098] Example 4 The only difference between this embodiment and embodiment 1 is that the parameters in step (2) and step (3) are different.

[0099] (2) Synthesis preparation stage: Pure water was added to the synthesis reactor to the set liquid level, stirring was started, and sodium hydroxide solution and ammonia solution were added at the same time. Finally, the bottom liquid conditions of the reactor were adjusted to alkalinity 10.0 g / L, pH 11.0, and temperature 50 °C. Nitrogen was introduced for protection, and ascorbic acid was added to the bottom liquid of the reactor at a concentration of 0.3 g / L (i.e., 0.3 g ascorbic acid was added to every 1 L of bottom liquid of the reactor). (3) Co-precipitation reaction stage: nickel, zinc, iron and manganese mixed metal salt solution, precipitant solution and complexing agent solution are added into the reactor in parallel to carry out co-precipitation reaction. Nitrogen protection is introduced during the co-precipitation reaction. The temperature of the reaction system is maintained at 50±0.5℃ and the alkalinity is 10.0g / L during the co-precipitation process. The precipitant is 10.5mol / L concentrated sodium hydroxide and the complexing agent is 8.0mol / L concentrated ammonia water.

[0100] The co-precipitation is divided into a nucleation stage and a particle growth stage; in the nucleation stage, the flow rate of the nickel-zinc-iron-manganese solution is 80 ml / min, the nucleation pH is maintained at 11.00-11.10, the rotation speed is 500 rpm, and the reaction time is 2.5 h to obtain precursor particles.

[0101] The pH value in the crystal nucleus growth stage was maintained at 10.50-10.70, and the alkalinity was 10.0 g / L. The particle growth stage was divided into two stages. The metal salt flow rate in the first stage of particle growth was 140 ml / min, the stirring speed in the first stage of particle growth was 450 rpm, and the reaction time in the first stage of particle growth was 6 h. The metal salt flow rate in the second stage of particle growth was 200 ml / min, the speed in the second stage of particle growth was 400 rpm, and the reaction time in the second stage of particle growth was 35-40 h.

[0102] The SEM image of the obtained precursor is shown in Figure 6 As shown, from Figure 6 It can be seen that after the alkalinity is increased, the sphericity of the sample and the morphology of the primary particles are improved.

[0103] Comparative Example 3 The only difference between this comparative example and Example 1 is that in step (3), the pH value in the nucleation stage is 11.80, and the pH value in the particle growth stage is 11.10.

[0104] The SEM image of the obtained precursor is shown in Figure 7 As shown, the SEM image of the precursor prepared in Comparative Example 1 ( Figure 3 )and Figure 4 It can be seen that with the increase of pH point in the nucleation stage, coupled with higher zinc ion concentration, very serious segregation occurs, resulting in a change in the particle growth trend.

[0105] Comparative Example 4 The only difference between this comparative example and Example 1 is that in step (3), the pH value in the nucleation stage is 10.4, and the pH value in the particle growth stage is 10.00.

[0106] The SEM image of the obtained precursor is shown in Figure 8 As shown, compared Figure 3 and Figure 8 It can be seen that as the pH point decreases, the effect of metal ion coprecipitation becomes worse, more free metal ions exist in the supernatant, and more fine particles appear on the surface of the sample.

[0107] Comparative Example 5 The only difference between this comparative example and Example 1 is that in step (3), the alkalinity is 25 g / L.

[0108] The SEM image of the obtained precursor is shown in Figure 9 As shown, compared Figure 3 and Figure 9 It can be seen that with the increase of alkalinity, the spherical morphology of the precursor secondary particles disappears and presents an irregular flake agglomeration state.

[0109] Comparative Example 6 The only difference between this comparative example and Example 1 is that in step (3), the alkalinity is 3 g / L.

[0110] The SEM image of the obtained precursor is shown in Figure 10 As shown, compared Figure 3 and Figure 10 It can be seen that with the decrease of alkalinity, the precursor particles become spherical, but the primary particles of the sample are thin and the sphericity is very poor.

[0111] Comparative Example 7 The difference between this comparative example and Example 1 is that, in step (1), in the solution preparation stage: a nickel-zinc-iron-manganese mixed metal sulfate solution is prepared according to a molar ratio of Ni:Zn:Fe:Mn of 23:8:33:36, and ascorbic acid is added to the solution at the same time, at a rate of 0.1 g of ascorbic acid per 1 L of the mixed metal sulfate solution, so that the total metal molar concentration in the solution is 2.0 mol / L.

[0112] In step (2), 0.5 g of ascorbic acid was added per 1 L of reactor bottom liquid.

[0113] In step (4), during aging, 0.25 g of ascorbic acid was added to the reaction slurry per 1 L of slurry.

[0114] from Figure 11 It can be seen that as the amount of antioxidant added to the metal salt solution decreases, the fine particles on the surface of the sample increase. After analysis, this may be because the antioxidant concentration in the metal salt solution is reduced, the oxidation degree of iron ions is increased, and the oxidized iron ions form separate crystal nuclei, which adhere to the particle surface during the growth process, resulting in a deterioration in the sphericity of the precursor particles.

[0115] Comparative Example 8 The only difference between this comparative example and Example 1 is that in step (4), during aging, 0.15 g of ascorbic acid was added to the reaction slurry per 1 L of slurry.

[0116] from Figure 12 It can be seen that small particles appear on the surface of the sample. After analysis, this may be because the addition of antioxidants during the aging stage can inhibit the oxidation of free metal ions, but due to the small amount added, some free ions are oxidized during the aging process and attached to the sample surface.

[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A sodium electric single crystal layered cathode material precursor, characterized in that: The chemical formula of the precursor is Ni x Fe y M (1-x-y-z) Mn z (OH)2, wherein 0.2≤x≤0.4, 0.2≤y≤0.5, 0.2≤z≤0.5, 0≤1-xyz≤0.1, and M is one or more of Cu, Zn, Ca, Mg, Al, Cr, and Cd; the precursor is a secondary particle sphere or spheroid composed of flake-shaped primary particles; the particle size D50 of the precursor is 3.5~10.0μm.

2. The sodium electric single crystal layered cathode material precursor according to claim 1, characterized in that: 0.03≤1-xyz≤0.08; Preferably, M is one or more of Cu and Zn; Preferably, the particle size D50 of the precursor is 3.5-7.0 μm.

3. A method for preparing a sodium electric single crystal layered cathode material precursor, characterized in that: include: (1) A mixed metal salt solution, an alkali solution and a complexing agent solution are introduced into the bottom liquid of a reaction kettle in parallel to perform a coprecipitation reaction; in the mixed metal salt solution, the metal elements are Ni x Fe y M (1-x-y-z) Mn z Ratio, wherein 0.2≤x≤0.4, 0.2≤y≤0.5, 0.2≤z≤0.5, 0≤1-xyz≤0.1, M is one or more of Cu, Zn, Ca, Mg, Al, Cr, Cd; an antioxidant is added to the mixed metal salt solution; The coprecipitation reaction includes a nucleation stage and a particle growth stage. During the coprecipitation reaction, the ammonia concentration of the reaction system is controlled to be 7-15 g / L; the pH value of the reaction system is controlled to be 11.00-11.40 in the nucleation stage to obtain a precursor seed material; the pH value of the reaction system is controlled to be 10.30-11.20 in the particle growth stage until the precursor seed material grows to a target particle size D50 to obtain a sodium electric precursor slurry; the pH value of the reaction system in the nucleation stage is higher than the pH value of the reaction system in the particle growth stage; (2) aging the precursor slurry, adding an antioxidant during the aging process, and continuously stirring. After the aging is completed, solid-liquid separation, washing and drying are performed to obtain the product.

4. The method for preparing a sodium electric single crystal layered cathode material precursor according to claim 3, characterized in that: In step (1), the antioxidant in the mixed metal salt solution is one or more of ascorbic acid, sodium citrate, isoascorbic acid and sodium isoascorbate; 0.15-0.3 g of antioxidant is added per 1 L of the mixed metal salt solution; Preferably, in step (2), the antioxidant is ascorbic acid; and during the aging process, 0.30-0.75 g of antioxidant is added per 1 L of the aged slurry.

5. The method for preparing a sodium electric single crystal layered cathode material precursor according to claim 3 or 4, characterized in that: In step (1), an antioxidant is added to the bottom liquid of the reaction kettle; the antioxidant is ascorbic acid; 0.15-0.5 g of antioxidant is added to every 1 L of the bottom liquid of the reaction kettle; Preferably, in step (1), the alkalinity of the reaction kettle bottom liquid is 7-15.0 g / L, the pH value is 10.30-11.40, and the temperature is 50±5°C.

6. The method for preparing a sodium electric single crystal layered cathode material precursor according to any one of claims 3 to 5, characterized in that: In step (1), the pH of the reaction system in the nucleation stage is 0.2-0.6 higher than the pH of the reaction system in the particle growth stage; Preferably, in step (1), the flow rate of the mixed metal salt solution in the nucleation stage is 60-100 ml / min; Preferably, in step (1), the flow rate of the mixed metal salt solution during the particle growth stage is 120-240 ml / min.

7. The method for preparing a sodium electric single crystal layered cathode material precursor according to any one of claims 3 to 6, characterized in that: In both step (1) and step (2), nitrogen protection is introduced; Preferably, in step (1) and step (2), the temperature of the reaction system is controlled at 49-55° C., and the stirring speed is controlled at 200-500 r / min.

8. The method for preparing a sodium electric single crystal layered cathode material precursor according to any one of claims 3 to 7, characterized in that: In step (1), the target particle size D50 of the precursor seed material in the nucleation stage is 0.5-1.8 μm; Preferably, in step (1), the reaction time of the nucleation reaction is 0.5 to 3.5 h; Preferably, in step (1), the target particle size D50 of the precursor in the particle growth stage is 3.5-10.0 μm.

9. A sodium electric single crystal layered positive electrode material, characterized in that: The precursor is prepared by mixing sodium with the precursor as claimed in claim 1 or 2 or the precursor prepared by the preparation method as claimed in any one of claims 3 to 8 and sintering.

10. A sodium ion battery, characterized in that It comprises the sodium electric single crystal layered positive electrode material as described in claim 9.

Citation Information

Patent Citations

  • Nickel-iron-manganese hydroxide and preparation method thereof

    CN115924993A

  • Positive electrode material precursor and preparation method thereof, positive electrode material for sodium ion battery and preparation method thereof, and sodium ion battery

    CN116081707A

  • Nickel-copper-iron-manganese quaternary sodium ion positive electrode material precursor and preparation method thereof

    CN117208973A

  • Quaternary precursor for sodium electricity and preparation method thereof

    CN117566814A

  • Sodium-ion battery positive electrode material precursor uniformly doped with stable valence state elements, preparation method thereof and sodium-ion battery positive electrode material

    CN117800411A

Cited By

  • Single-crystal positive electrode material as well as preparation method and application thereof

    CN120749145A